Part-Time Farming, Diseases and Pest Control Delay and Its External Influence on Pesticide Use in China’s Rice Production - Fang, Chenliang; Xu, Yongqin; Ji, Yueqing (Frontiers in Environmental Science, 2022)
This paper uses track data on paddy field production in 20 villages in 5 counties in central Jiangsu of China to analyze the causes of delay in rice pest control and its external effects. The results show that living outside village of labors will increase the probability of delay in prevention and control of diseases and pest, while the increase of farm size and the development of outsourcing services and public monitoring and forecasting services will help reduce the probability of delay. The results also show that the delay in rice diseases and pest control has negative externalities. The delays of other farmers in the village will significantly increase the frequency of pesticide use. These results highlight important policy implications for the development of large-scale farming and the development of diseases and pest control services in rice production.